تحليل السبك النحوي في سورة لقمان: (دراسة تحليلية نصية) - Farah Adilah Fajrin (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
To understand a text, it is easier to pay attention to the grammatical elements contained therein first, so it is necessary to interpret an element that discusses the harmony and attachment of structural relationships between one utterance and another. Among them is the usage of grammatical cohesion, because it is related to the meaning that will be produced in a discourse. Which are usually marked with, references, substitutions, ellipsis and conjunctions. Therefore this study will review the grammatical cohesion in the Surah Luqman. The method used is descriptive qualitative which will produce data in the form of sentences from the text of the Surah Luqman, with Al-Quran Al-Karim as data sources, while using a text analysis approach. The problems examined in this study are: 1) What are the grammatical cohesion devices in the Surah Luqman. 2) What is the form of the grammatical cohesion device in Surah Luqman. Based on the results of the research, it has been found that in Surah Luqman there are elements of grammatical cohesion, namely Reference (Al-Ilahah) totaling 424 words, Substitution (Al-istibdal) totaling 7 words, Ellipsis (Al-hadzfu) 3 words and conjunctions (Al-wushlu) totaling 72 words.